The golden age?: What the 100 most cited articles in terrorism studies tell us - Silke, Andrew (Terrorism and political violence, 2017)
In a context where widespread failings in the nature of terrorism research are well recognised—yet where the quantity of work is still enormous—is it possible to fairly assess whether the field is progressing or if it has become mired in mediocre research? Citation analysis is widely used to reveal the evolution and extent of progress in fields of study and to provide valuable insight into major trends and achievements. This study identifies and analyses the current 100 most cited journal articles in terrorism studies. A search was performed using Google Scholar for peer-reviewed journal articles on subjects related to terrorism and counter-terrorism. The most cited articles were published across sixty-two journals, which reflected the interdisciplinary nature of terrorism studies. Compared to other articles, the most cited articles were more likely to be the result of collaborative research and were also more likely to provide new data. Sixty-three of the top 100 articles have been published since 2001. The findings are discussed in relation to the evolution of terrorism research and current debates on progress in the field.